DECOMPOSITION METHOD FOR FORECASTING THE NUMBER OF PARTICIPANTS OF NEW FAMILY PLANNING IN SURABAYA - Dinana Izzatul Ulya; Mahmudah Mahmudah (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2020)
Indonesia is a country that has a large population and Family Planning Program was initially designed to control the population. This study aimed to forecast new Family Planning Program participants in the city of Surabaya in 2019 using the decomposition method. This study used secondary data, which is the number of participants for new Family Planning Program in January 2014 to December 2018 (60 plots of data) obtained from the PCWECP Surabaya. The researcher chose decomposition method in this study because decomposition is a one-time series method that has rarely been applied in a research. Based on the results of the study, the number of participants for new Family Planning Program from January to December 2019 was 2,776; 2,663; 2,504; 2,340; 2,440; 1,912; 2,034; 2,291; 2,223; 2,123; 2,123; 2,130 and 2,560 participants. The error value generated by this study is MAPE of 9, MAD of 365, MSD 197,738, and MSE of 2.1675. The best error value is the one that has the smallest value, so the MSE is the best model.